PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA PHET SIMULATION TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Andria Sukmawati, Vika; Rahayu, Puji; Permas Hikmatunisa, Nenden (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the effect of the Contextual Teaching and Learning (CTL) model supported by PhET Simulation media on elementary school students' understanding of mathematical concepts in the topic of fractions. The research method used is a quasi-experimental, utilizing a Nonequivalent Control Group Design. The participants included students from class IVB, serving as the experimental group, and class IVC as the control group in an elementary school located in Purwakarta Regency. Analysis of the data indicates that the experimental group, which was instructed using the CTL model supported by PhET Simulation media, showed a notable improvement in their understanding of mathematical concepts compared to the control group, which followed traditional teaching methods. This is evidenced by the N-Gain test scores, where the experimental class achieved an average score of 61.13%, while the control class obtained an average of 44.90%. Additionally, implementing the CTL model with PhET Simulation media resulted in a 15. 9% increase in students' comprehension of mathematical concepts. In summary, the findings suggest that the experimental group displayed enhanced understanding of mathematical concepts following the application of the CTL model, indicating a positive impact of the CTL model on their learning.